Transformative potential of digital systems for promoting human-wildlife coexistence: A systematic literature review - Bas S. H. T. Michielsen; Gerard Schouten; Joris P. G. Cromsigt; Remco C. Veltkamp; Irma Arts; Jitse Bijlmakers; Magali Frauendorf; Tim R. Hofmeester; Amy Newsom; Minh-Xuân A. Truong; Helen Verploegen; Els Weinans; et al. (Ambio, 2026)
Digital technology plays an increasingly important role in wildlife management and conservation, by enhancing monitoring capabilities and reshaping human-wildlife interactions. However, the transformative potential of these digital solutions for coexistence remains unclear. This paper presents a novel framework to assess the transformative potential of digital systems in wildlife management and conservation, focusing on two key factors: Digital Maturity, which evaluates technical sophistication of digital systems, and Systemic Depth, which measures their capacity for enabling lasting change. We used this framework to evaluate 524 studies in a systematic literature review in wildlife management and conservation, and found that although sometimes higher Digital Maturity or Systemic Depth was achieved, overall the transformative potential of applied digital systems was still low. Studies that scored high emphasize interdisciplinary collaboration, adaptability, data sharing, and technologies such as machine learning. This research highlights achieving transformative potential requires a holistic approach integrating ecological, social, and technological perspectives.

Ion mobility spectrometer with heated sample inlet - Solution to the issue of temperature effect on resolving power - Martin Lippmann; Moritz Hitzemann; Timo Sawatzki; Jonas Winkelholz; Alexander Nitschke; Tim Kobelt; Stefan Zimmermann (Analytica Chimica Acta, 2025)

Comparison of two different integration methods for the (1+1)-dimensional Schrödinger-Poisson equation - Nico Schwersenz; Victor Loaiza; Tim Zimmermann; Javier Madroñero; Sandro Wimberger (Computer Physics Communications, 2024)

Constant power threshold—predicting maximal lactate steady state in recreational cyclists - Christian Vobejda; Tim Wortmann; Elke Zimmermann (German Journal of Exercise and Sport Research, 2023)
Introduction Prolonged time trials proved capable of precisely estimating anaerobic threshold. However, time trial studies in recreational cyclists are missing. The aim of the present study was to evaluate accuracy and viability of constant power threshold, which is the highest power output constantly maintainable over time, for estimating maximal lactate steady state in recreational athletes. Methods A total of 25 recreational athletes participated in the study of whom 22 (11 female, 11 male) conducted all constant load time trials required for determining constant power threshold 30 min and 45 min, which is the highest power output constantly maintainable over 30 min and 45 min, respectively. Maximal lactate steady state was assessed subsequently from blood samples taken every 5 min during the time trials. Results Constant power threshold over 45 min (175.5 ± 49.6 W) almost matched power output at maximal lactate steady state (176.4 ± 50.5 W), whereas constant power threshold over 30 min (181.4 ± 51.4 W) was marginally higher ( P = 0.007, d = 0.74). Interrelations between maximal lactate steady state and constant power threshold 30 min and constant power threshold 45 min were very close (R 2 = 0.99, SEE = 8.9 W, Percentage SEE (%SEE) = 5.1%, P < 0.001 and R 2 = 0.99, SEE = 10.0 W, %SEE = 5.7%, P < 0.001, respectively). Conclusions Determination of constant power threshold is a straining but viable and precise alternative for recreational cyclists to estimate power output at maximal lactate steady state and thus maximal sustainable oxidative metabolic rate.

European beewolf (Philanthus triangulum) will expand its geographic range as a result of climate warming - Piotr Olszewski; Marcin K. Dyderski; Łukasz Dylewski; Petr Bogusch; Christian Schmid-Egger; Toshko Ljubomirov; Dominique Zimmermann; Romain Le Divelec; Bogdan Wiśniowski; Lucyna Twerd; Tadeusz Pawlikowski; Maurizio Mei; et al. (Regional Environmental Change, 2022)
Climate change is an important driver of the spread of apiary pests and honeybee predators. These impact on one of the economically most important pollinators and thus pose serious threats to the functioning of both natural ecosystems and crops. We investigated the impact of the predicted climate change in the periods 2040–2060 and 2060–2080 on the potential distribution of the European beewolf Philanthus triangulum , a specialized honeybee predator. We modelled its potential distribution using the MaxEnt method based on contemporary occurrence data and bioclimatic variables. Our model had an overall good performance (AUC = 0.864) and the threshold of occurrence probability, assessed as the point with the highest sum of sensitivity and specificity, was at 0.533. Annual temperature range (69.5%), mean temperature in the warmest quarter (12.4%), and precipitation in the warmest quarter (7.9%) were the principal bioclimatic variables significantly affecting the potential distribution of the European beewolf. We predicted the potential distribution shifts within two scenarios (optimistic RPC4.5 and pessimistic RCP8.5) and three Global Circulation Models (HadGEM2-ES, IPSL-CM5A-LR, and MPI-SM-LR). Both optimistic and pessimistic scenarios showed that climate change will significantly increase the availability of European beewolf potential niches. Losses of potential niches will only affect small areas in southern Europe. Most of the anticipated changes for the period 2060–2080 will already have occurred in 2040–2060. The predicted range expansion of European beewolf suggests that occurrence and abundance of this species should be monitored.

Oral mannitol for bowel preparation: a dose-finding phase II study - Cristiano Spada; Giancarla Fiori; Peter Uebel; Gian Eugenio Tontini; Paola Cesaro; Leonardo Minelli Grazioli; Pietro Soru; Ivana Bravi; Carsten Hinkel; Alberto Prada; Dhanai Di Paolo; Tim Zimmermann; et al. (European Journal of Clinical Pharmacology, 2022)
Background Successful bowel preparation (BP) for colonoscopy depends on the instructions, diet, the laxative product, and patient adherence, which all affect colonoscopy quality. Nevertheless, there are no laxatives which combine effectiveness, safety, easy self-administration, good patient acceptance, and low cost. However, mannitol, a sugar alcohol, could be an attractive candidate for use in clinical practice if it is shown to demonstrate adequate efficacy and safety. Aims The present phase II dose-finding study compared three doses of mannitol (50, 100, and 150 g) to identify the best dose to be used in a subsequent phase III study. Methods The Boston Bowel Preparation Scale, caecal intubation rate, adherence, acceptability, and safety profile, including measurement of potentially dangerous colonic gas concentrations (CH 4 , H 2 , O 2 ), were considered in all patients. A weighted algorithm was used to identify the best mannitol dose for use in the subsequent study. Results The per-protocol population included 60 patients in the 50 g group, 54 in the 100 g group, and 49 in the 150 g group. The 100 g dose was the best as it afforded optimal colon cleansing efficacy (94.4% of patients had adequate BP), adherence, acceptability, and safety, including negligible gas concentrations. Conclusions The present study demonstrated that the colon cleansing efficacy and safety of mannitol were dose dependent. Conversely, gas concentrations were not dose dependent and negligible in all patients. Combined evaluation of efficacy, tolerability, and safety, using a weighted algorithm, determined that mannitol 100 g was the best dose for the phase III study.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Exposure-response modeling improves selection of radiation and radiosensitizer combinations - Tim Cardilin; Joachim Almquist; Mats Jirstrand; Astrid Zimmermann; Floriane Lignet; Samer El Bawab; Johan Gabrielsson (Journal of Pharmacokinetics and Pharmacodynamics, 2022)
A central question in drug discovery is how to select drug candidates from a large number of available compounds. This analysis presents a model-based approach for comparing and ranking combinations of radiation and radiosensitizers. The approach is quantitative and based on the previously-derived Tumor Static Exposure (TSE) concept. Combinations of radiation and radiosensitizers are evaluated based on their ability to induce tumor regression relative to toxicity and other potential costs. The approach is presented in the form of a case study where the objective is to find the most promising candidate out of three radiosensitizing agents. Data from a xenograft study is described using a nonlinear mixed-effects modeling approach and a previously-published tumor model for radiation and radiosensitizing agents. First, the most promising candidate is chosen under the assumption that all compounds are equally toxic. The impact of toxicity in compound selection is then illustrated by assuming that one compound is more toxic than the others, leading to a different choice of candidate.

Anti-necrotic and cardioprotective effects of a cytosolic renin isoform under ischemia-related conditions - Heike Wanka; Doreen Staar; Philipp Lutze; Barbara Peters; Johanna Hildebrandt; Tim Beck; Inga Bäumgen; Alexander Albers; Thomas Krieg; Katrin Zimmermann; Jaroslaw Sczodrok; Simon Schäfer; et al. (Journal of Molecular Medicine, 2016)

Identification of RARRES1 as a core regulator in liver fibrosis - Andreas Teufel; Diana Becker; Susanne N. Weber; Steven Dooley; Katja Breitkopf-Heinlein; Thorsten Maass; Katrin Hochrath; Markus Krupp; Jens U. Marquardt; Martin Kolb; Bernhard Korn; Christof Niehrs; et al. (Journal of Molecular Medicine, 2012)